The impact of innovator types on export performance in the Argentine wine industry - Depetris Chauvin, Nicolas Manuel (2025)
Purpose: The article explores the impact of innovators’ profiles on export outcomes within the Argentine wine industry. The objective is to identify and estimate how different types of innovators influence the success of Argentine wines in international markets.Design/methodology/approach: The article utilizes a representative sample of 230 wineries and combines a comprehensive survey with Inverse Probability Weighted Regression Adjustment to address selection bias and estimate causal effects. Findings: The analysis reveals that wineries managed by "extremely conceptual" (EC) innovators -those who introduce radical, disruptive changes and plan and execute innovations with detailed foresight- demonstrate superior export performance compared to those led by other innovators. EC innovators are prevalent among exporting firms and are associated with higher export value shares and lower domestic sales proportions.Research limitations/implications: The article is limited by its cross-sectional nature, which restricts dynamic analysis. Additionally, survey responses may not consistently reflect past innovation activities. Future research could address these limitations through longitudinal studies and ensure consistent respondent profiles for deeper insights into innovation dynamics.Practical implications: The findings suggest that focusing on conceptual innovation strategies can enhance export performance in the wine industry. Wineries aiming to succeed in international markets may benefit from adopting detailed planning and strategic innovation approaches.Originality/value: The article provides new insights into how different innovator profiles impact export outcomes in the Argentine wine industry. By distinguishing between types of innovators and their effects on international market performance, the research offers valuable implications for wineries seeking to enhance their global competitiveness.